HUBUNGAN DIPLOMASI KEAMANAN INGGRIS DAN UNI EROPA (UE) PASCA PERNYATAAN REFERENDUM BRITISH EXIT (BREXIT) TAHUN 2016-2017 - Tobing, Ledi Sanita; Saeri, M. (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This study explains about how the security diplomacy of the United Kingdom and the European Union after the Brexit Referendum (British Exit) conducted by the United Kingdom in 2016-2017. Brexit is carried out by the United Kingdom because the United Kingdom found it was no longer compatible with the European Union policy. This study uses a Neo-realist perspective by Kenneth N. Waltz quoted from his book Theory of International Politics, and supported by diplomatic theory, and the level of analysis of the State. Furthermore, the methodology used in this study is a qualitative research methodology which the data collection techniques uses the literature review method. The results of this study indicate that the United Kingdom needs to conduct broader negotiations after the statement of the Brexit Referendum on foreign policy and security issues, especially in the European region where the European Union is an important player in the European region. And negotiate on how Britain sees, whether British policy is in accordance with EU policy. So that in this case the United Kingdom needs to discuss its security issues in order to remain in line with the European Union, when the United Kingdom has been declared officially out of the European UnionKeywords: Brexit (British Exit), Security Diplomacy, European Union, Negotiation.Â